2016
DOI: 10.1104/pp.16.01641
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Mitochondrial Protein Phosphatase SLP2 by MIA40 Regulates Seed Germination

Abstract: Reversible protein phosphorylation catalyzed by protein kinases and phosphatases represents the most prolific and wellcharacterized posttranslational modification known. Here, we demonstrate that Arabidopsis (Arabidopsis thaliana) Shewanella-like protein phosphatase 2 (AtSLP2) is a bona fide Ser/Thr protein phosphatase that is targeted to the mitochondrial intermembrane space (IMS) where it interacts with the mitochondrial oxidoreductase import and assembly protein 40 (AtMIA40), forming a protein complex. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
0
13
1
Order By: Relevance
“…Similar (low) copy numbers of both the kinase and the phosphatase per mitochondrion may be regarded as further evidence for their function as a regulatory couple. Another phosphatase, SLP2, which is present in the IMS, and involved in the regulation of seed germination (Uhrig et al ., ), was detected at comparably low copy number (296 copies).…”
Section: Resultsmentioning
confidence: 97%
“…Similar (low) copy numbers of both the kinase and the phosphatase per mitochondrion may be regarded as further evidence for their function as a regulatory couple. Another phosphatase, SLP2, which is present in the IMS, and involved in the regulation of seed germination (Uhrig et al ., ), was detected at comparably low copy number (296 copies).…”
Section: Resultsmentioning
confidence: 97%
“…A recent study showed that A. thaliana MIA40 activates the phosphatase activity of an IMS‐located Shewanella‐like protein phosphatase 2 (SLP2), not found in yeast and humans, by promoting the formation of an intramolecular disulfide bridge. This interaction is important for regulating some gibberellic acid‐dependent processes during seed formation (Uhrig et al ., ).…”
Section: The Disulfide Relay In the Mitochondrial Intermembrane Spacementioning
confidence: 99%
“…MIA40 is one of two components of the mitochondrial intermembrane space (IMS) disulfide relay system, which ensures import of Cys-containing proteins into the IMS (Herrmann and Riemer, 2012). Arabidopsis MIA40 resides in the IMS and peroxisomes and is thought to be responsible for importing and trapping the chaperone for Mn-superoxide dismutase (CCS1), Cu/ Zn superoxide dismutase 1 (CSD1), and Shewanella-like protein phosphatase 2 (SLP2) in the IMS and the Cu/Zn CSD3 in peroxisomes (Carrie et al, 2010;Uhrig et al, 2017). Peroxisome localization has only been observed using GFP-MIA40-N terminus fusion constructs that block MYR.…”
Section: Alternative Localization Of Myred Proteins In Non-pm Compartmentioning
confidence: 99%